A Reality Group Counselling to Reduce Cheating Habit in High School Students - Pratiwi, Titin Indah; Habsy, Bakhrudin All; Arfiyani, Maulidia Putri; Khusumadewi, Ari (Universitas Negeri Padang, 2024)
Cheating behavior often arises due to a lack of individual self-control, influenced by both internal and external pressures, as well as the presence of opportunities to engage in dishonest actions. To address this issue, a pre-experimental study was conducted utilizing a one-group pretest-posttest design to evaluate the effectiveness of reality group counseling in reducing cheating behavior among high school students. After administering the intervention, the students were re-assessed, and the results were analyzed using a paired T-test. The findings revealed that the calculated t-value was 6.350, which exceeded the critical value of 3.82 at a 5% significance level with 3 degrees of freedom. Additionally, the significance value (2-tailed) was 0.008, which was lower than the threshold of 0.05. Based on these results, the null hypothesis (Ho) was rejected, and the alternative hypothesis (Ha) was accepted, indicating a significant difference in students' cheating behavior before and after the counseling intervention. These findings suggest that reality group counseling was effective in reducing cheating habits among the high school students who participated in the study. In conclusion, reality group counseling can be considered a beneficial approach for mitigating cheating behavior in educational settings, contributing to the promotion of academic integrity.